The Effectiveness of Poly-(4-vinyl-N-hexylpyridiniumbromide) as an Antibacterial Implant Coating: An In Vitro Study - L. Ringenberg; A. Winkel; O. Kufelt; P. Behrens; M. Stiesch; W. Heuer (International Journal of Dentistry)
The clinical success of osseointegrated dental implants depends on the strong attachment of the surrounding hard and soft tissues. Bacterial adhesion on implant surfaces can cause inflammatory reactions and may influence healing and long-term success of dental implants. Promising implant coatings should minimize bacterial adhesion, but allow epithelial and connective tissue attachment. Therefore, the present study has examined the bioactive effect of poly-(4-vinyl-N-hexylpyridiniumbromide) regarding typical oral bacteria as well as cytotoxicitiy to human cells considering different methods of connecting polymers to silicate-containing surfaces. The results revealed that the application of putative antibacterial and biocompatible polymer in coating strategies is affected by a variety of parameters. Published findings regarding reduced bacterial adhesion could not be verified using oral pathogens whereas hexylated polymers seem problematic for strong adhesion of soft tissue. Concerning innovative coatings for dental implants basic aspects (surface roughness, thickness, alkylation, combination with other polymers) have to be considered in further investigations.